DYNAMICS OF THE GENDER DEVELOPMENT INDEX AND GENDER EMPOWERMENT INDEX IN BENGKULU CITY 2019–2023: AN ANALYSIS OF LOCAL FACTORS BASED ON STATISTICAL DATA - Nabila Fatihah Cecellia Putri Hasibuan; Heni Nopianti; Diyas Widiyarti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the dynamics of the Gender Development Index (GDI) and Gender Empowerment Index (GEI) in Bengkulu City from 2019 to 2023 and identifies local factors influencing their changes. Using a quantitative descriptive approach and secondary data from the Bengkulu Province Central Bureau of Statistics (BPS), the analysis focuses on GDI dimensions such as health, education, and economy and GEI determinants such as women’s participation in parliament, income contribution, and professional representation. The study employs a gender and development framework to interpret equality progress and policy implications. Findings reveal that Bengkulu City’s GDI increased by 0.15 points, reaching 96.12 in 2023, indicating improved gender parity in development outcomes. Conversely, the GEI decreased by 4.41 points to 75.94, highlighting persistent challenges in women’s empowerment, particularly in politics and professional sectors. Contributing factors include limited female representation in parliament, fluctuating women’s income contributions due to the rise of female breadwinners, and the persistence of the glass ceiling restricting women’s career advancement. These findings suggest that while gender equality in basic development indicators has improved, empowerment dimensions remain constrained, emphasizing the need for targeted and sustainable gender-responsive policies.